Legitimation of the simplifying consensus formulas for criminal processing - Brousset Salas, Ricardo Alberto (2009)
In view of the material impossibility that all actions received by the criminal justice system can be subject to linear common proceedings, the simplification methods become of vital importance within criminal development itself, which facilitate the anticipated conclusion of the proceeding upon agreement. The Peruvian Code of Criminal Procedures has developed two methods: an anticipated conclusion of a lawsuit and the so-called plea bargaining or anticipated conclusion proceeding, both of general application and with no limitations as to the punishments to be imposed by prosecution. These are developed by the author, proposing certain conditions that would make them feasible